Study of g protein-coupled receptor (gpcr) homo- and heteroreceptor complexes interactions in the central nervous system through proximity labelling techniques - Pita-Rodríguez, Mariana (UMA Editorial, 2024)
There exists substantial evidence for the existence of GPCR homo and heteroreceptor complexes with allosteric receptor-receptor interactions in the Central Nervous System (CNS). Through the receptor heteromerization the allosteric receptor-receptor interactions can develop and produce alterations in recognition including novel allosteric binding sites, pharmacology, signaling, and trafficking of the participating receptors (receptor protomers). However, there is also lack of knowledge on the stoichiometry of the participating receptor protomers in GPCR heteroeceptor complexes. Therefore, the overall aim of this thesis was to gain insight into molecular aspects of several adenosine A2AR and dopamine D2R heteroreceptor complexes and their allosteric receptor-receptor interaction in the Central Nervous System, with special emphasis on the role of the balance between their homo and heteroreceptor complexes. As a proof of concept, we optimized and used the situ Proximity Ligation Assays methods to study A2AR and D2R iso, homo and heteroreceptor complexes. Our findings from our in situ PLA analysis revealed the highest densities of A2AR-A1R isoreceptor complexes and A2AR-A2AR homoreceptor complexes in the pyramidal cell layers of CA1-CA3 and the polymorphic cell layer in the hilus of the dentate gyrus in the hippocampus. Based on these observations, we propose that the regulation of adenosine A2AR signaling in the hippocampus relies on a balance between A2AR-A2AR homoreceptor complexes and A1R-A2AR isoreceptor complexes. Dysregulation of adenosine signaling within these complexes, particularly in the CA3-CA1 regions, may contribute to pathological outcomes such as psychosis or depression by modulating the interactions of the GABA-glutamate network.
Additionally, we have confirmed the formation of A2AR-D4R complexes through BRET1 techniques in HEK cells, highlighting the lower effectiveness of the A2AR and D4.7R splice variant receptors in heteromer formation. Interestingly, our research expands on the heteroreceptor complexity by demonstrating, for the first time, that A2A receptors can form heteroreceptor complexes with the common human dopamine D4.xR polymorphism variants (D4.2R, D4.4R, and D4.7R) to varying degrees in HEK293T cells co-transfected with both receptor types. Moreover, through in situ PLA, we provide evidence for the existence of A2AR-D4R heteroreceptor complexes in several regions of the rat brain. Also, by employing advanced techniques such as in situ proximity ligation assay (PLA) and Bioluminescence Resonance Energy Transfer (BRET), we have provided evidence for the existence of D2R and D4R complexes with alpha-synuclein in the rat brain, specifically in the dorsal and ventral striatum. Moreover, we have validated the presence of alpha-synuclein complexes with A2AR and DAT, further implicating these interactions in the pathophysiology of PD. Notably, our findings demonstrate an increase in D2R-alpha-synuclein and DAT-alpha-synuclein interactions in the BSSG animal model of PD, highlighting the potential role of these interactions in disease progression. Overall, our proximity ligation assays studies provide compelling evidence for the significance of GPCR iso- homo- and heteroreceptor complexes in modulating synaptic transmission and neuroplasticity in the hippocampus and other important areas of the brain. These findings could potentially lead to the development of innovative therapeutic strategies for neurological conditions associated with synaptic dysfunction and neurodegeneration.
Keywords: Dopamina - Receptores; Adenosina - Receptores; Neurociencias; G protein-coupled receptors; In situ Proximity ligation assay; Adenosine A2A receptor; Dopamine D4 receptor; Heteroreceptor complexes